2018
DOI: 10.1186/s40068-018-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of future climate and land use/cover change on water resources in the Ndembera watershed and their mitigation and adaptation strategies

Abstract: Background: Land use/cover and climate changes have a great influence on the hydrological processes in the watershed. The impacts of land use/cover and climate change are set to increase in the future due to the increased clearance of virgin forest lands for agriculture and the rise of global warming. The way in which the future climate will interact with the land use changes and affect the water balance in the watersheds requires more attention. This study was carried out in the Ndembera river watershed in Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 49 publications
0
36
1
3
Order By: Relevance
“…SWAT has been used to assess the impacts of anthropogenic activities that degenerate the natural river basin systems and thus impacting the water balance of a watershed [57,58]. In recent years, SWAT has been widely used to simulate watershed hydrological processes in many countries [21,52,53,59,60].…”
Section: Soil and Water Assessment Tool (Swat)mentioning
confidence: 99%
See 1 more Smart Citation
“…SWAT has been used to assess the impacts of anthropogenic activities that degenerate the natural river basin systems and thus impacting the water balance of a watershed [57,58]. In recent years, SWAT has been widely used to simulate watershed hydrological processes in many countries [21,52,53,59,60].…”
Section: Soil and Water Assessment Tool (Swat)mentioning
confidence: 99%
“…Kilimanjaro. SWAT has been tested and used to solve complex watershed management problems in many regions all over the world [21,47,[51][52][53]. Therefore, the objectives of this paper are three-fold viz: to set up, parameterize and calibrate the SWAT model in terms of streamflow.…”
Section: Introductionmentioning
confidence: 99%
“…There exist limited studies [28][29][30][31][32] that have demonstrated the impact of climate and land use change on the hydrological processes in the wetland-catchment nexus in East Africa. Yet, this information is vital to evaluate the possible vulnerability and resilience of these ecosystems to climate change, in particular the impacts of low predictability of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable with those from Woldesenbet et al (2018) in the Upper Blue Nile basin, Ethiopia and Bossa et al (2014) in the West Africa region. The increase in ET due to forest expansion has been reported by Hyandye et al (2018), wherein they found that forest expansion (+7%) in Ndembera watershed located in Tanzania increased ET by approximately 8%.…”
Section: The Impact Of Land-use Change On Hydrological Responsementioning
confidence: 62%
“…In recent years, many studies examined the combined impact of land-use and climate change on hydrologic processes (Koch et al , 2015;Hyandye et al , 2018;Aboelnour et al , 2019). The findings from these studies consistently highlight the water balance components including streamflow, surface runoff, groundwater, and evapotranspiration are likely to be impacted by future land-use and climatic changes.…”
Section: Introductionmentioning
confidence: 95%